2020
DOI: 10.1139/cjpp-2019-0349
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic acid B exerts a protective effect in acute liver injury by regulating the Nrf2/HO-1 signaling pathway

Abstract: Salvianolic acid B (Sal B) exerts strong antioxidant activity and eliminates the free radical effect. However, how it affects the antioxidant pathway is not very clear. The objective of this study was to investigate the underlying mechanism of Sal B in CCl4-induced acute liver injury, especially its effect on the Nrf2/HO-1 signaling pathway. For the in vivo experiment, an acute liver injury model was induced using CCl4 and treated with Sal B. For the in vitro experiment, an oxidative damage model was establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…49,50 NQO1 is a highly inducible phase II enzyme with superoxide scavenging properties and plays a critical role in detoxification metabolism. 51,52 In our current study, AKP pretreatment significantly increased the low expressions of Nrf2 and pNrf2 proteins and downstream proteins HO-1 and NQO1 in mouse liver tissues induced by CCl 4 exposure. A previous study found that a tetrapeptide identified from Chinese Baijiu played an antioxidant role by promoting nuclear translocation of Nrf2 after its phosphorylation and inhibiting its ubiquitination in HepG2 cells.…”
Section: Discussionsupporting
confidence: 58%
“…49,50 NQO1 is a highly inducible phase II enzyme with superoxide scavenging properties and plays a critical role in detoxification metabolism. 51,52 In our current study, AKP pretreatment significantly increased the low expressions of Nrf2 and pNrf2 proteins and downstream proteins HO-1 and NQO1 in mouse liver tissues induced by CCl 4 exposure. A previous study found that a tetrapeptide identified from Chinese Baijiu played an antioxidant role by promoting nuclear translocation of Nrf2 after its phosphorylation and inhibiting its ubiquitination in HepG2 cells.…”
Section: Discussionsupporting
confidence: 58%
“…These cancer driver genes give cells a growth advantage, especially when they are mutated or otherwise dysregulated. In this study, we used the DriverDBv3 ( Jin et al, 2020 ) that uses 12 algorithms, such as ActiveDriver ( Reimand and Bader, 2013 ), CoMET ( Martin et al, 2015 ), Dendrix ( Vandin et al, 2012 ), DriverML ( Han et al, 2019 ), DriverNet ( Bashashati et al, 2012 ), e-Driver ( Porta-Pardo and Godzik, 2014 ), iPAC ( Ryslik et al, 2013 ), MEMo ( Ciriello et al, 2013 ), MSEA ( Jia et al, 2014 ), MUTEX ( Babur et al, 2015 ), NetBox ( Cerami et al, 2010 ), and OncodriveCLUST ( Tamborero et al, 2013 ), to predict the cancer driver genes.…”
Section: Methodsmentioning
confidence: 99%
“…Although salvianolic acid can directly scavenge free radicals, they may not be present in the body at a high concentration ( 49 ). The antioxidant activity of salvianolic acid may increase the expression of antioxidant enzymes by activating nuclear factor E2-related factor 2 (Nrf2)/heme oxygenase-1 (HO-1) signaling pathway ( 9 ), thus reducing the expression of peroxidase ( 50 ).…”
Section: Active Ingredients Of Salvia Miltiorrhizamentioning
confidence: 99%